Utilización del zapallo (Cucúrbita máxima y Cucúrbita Pepo), en la elaboración de compotas, Quevedo – Los Ríos 2013. - Castro Ramírez, Luis Arturo (2013)
This research was conducted at the Experimental Farm " La María " , owned by State Technical University Quevedo ( UTEQ ) located in the 7 ½ miles of track Quevedo - El Empalme . The investigation lasted 30 days 2x3 factorial arrangement ( 2 ( pumpkin ) x 3 ( formulations) ) , in a randomized block design (DBA ) with 5 replications was applied . For comparison between treatment means by Tukey test (p ≤ 0.05) was used. The variables analyzed in this experiment were: Physical-chemical analysis: Degrees Brix, viscosity, protein, acidity and Ph. Microbiological analysis: Total aerobes, yeasts, fungi. Analysis of sensory profile: Smell, Taste, Color and Texture: To validate the acceptance of treatments the major internal and external features such as assessed. Results: The amount of sugar in each of the jams modified and accentuated the flavor and viscosity for each prototype, presenting sweetest jams and intermediate viscosities. The viscosity was effective in presenting the physical parameter consistency for sauce, also took effect increasing the viscosity of both jams. The prototype was accepted Pepo squash with a rating of "Good" filling 100% of the value tasted by panelists.